Triglyceride-Rich Lipoproteins and Their Remnants as Silent Promoters of Atherosclerotic Cardiovascular Disease and Other Metabolic Disorders: A Review - Sascău, Radu (Nutrients, 2021)
While targeting elevated serum levels of low-density lipoprotein cholesterol has been the mainstay of atherosclerosis prevention and treatment for decades, the evidence regarding the atherogenic role of hypertriglyceridemia is still controversial. Various epidemiological population-based studies on statin-treated subjects nominated triglycerides, triglyceride-rich lipoproteins (namely, chylomicrons and very-low-density lipoprotein particles), and their remnants as major determinants of the substantial residual cardiovascular risk. With the triglyceride-glucose index and triglyceride to high-density lipoprotein ratio emerging as surrogate indicators of peripheral artery disease and atherosclerotic cerebrovascular disease, one can conclude that further research addressing the intricate relationship between triglycerides and atherosclerosis is warranted. Therefore, this review aims to provide insight into the current clinical and epidemiological state of knowledge on the relationship between triglycerides and atherosclerotic cardiovascular disease. It also intends to highlight the connection between triglycerides and other metabolic disorders, including diabetes mellitus, and the potential benefits of triglyceride-lowering agents on cardiovascular outcomes and all-cause mortality.